Optimization of Practicum-Based Science Learning through Science KIT Training for Teachers at Junior High School 8 Makassar - St. Mutia Alfiyanti Muhiddin; Sitti Saenab; Arie Arma Arsyad; Andi Rahmat Saleh; Agussalim A (Yayasan Daarul Huda Kruengmane, 2026)
This activity aims to optimize practicum-based science learning through the utilization of Science Kits (KIT IPA) at State Junior High School 8 Makassar. The problem faced by science teachers at the school was their limited experience in using Science Kits optimally, particularly the Optics Kit and the Electricity and Magnetism Kit, resulting in less effective practicum implementation. The training was conducted through a workshop approach consisting of kit usage demonstrations, hands-on practice, and assistance in developing experiment-based student worksheets (LKPD). The results of the activity showed an improvement in teachers’ understanding of the functions and procedures for using Science Kits, as well as an increase in science teachers’ ability to design practicum activities aligned with learning outcomes. In addition, participants applied the simple practicum modules developed during the training to be implemented in classroom learning. This activity contributed to improving the quality of science learning at State Junior High School 8 Makassar and strengthening teachers’ competencies in conducting active, contextual, and inquiry-based learning.